Implementasi Layanan Bimbingan dan Konseling di SMAN 3 Karawang - Mutia Nurnabilla; Ramadhan Dwi Saputra; Reva Fadhillah; Safira Nur Azizah; Nur Aini Farida (CV. Kayaswara, 2025)
ABSTRACT Guidance and Counseling (BK) services are an integral part of the education system that function to assist students in developing their potential, adapting to their environment, and overcoming personal, social, academic, and career-related problems. According to Prayitno (2004) and Tohirin (2011), BK services encompass the functions of understanding, prevention, alleviation, and development, all of which aim to support students’ optimal growth and development. This study aims to examine the implementation of BK services at SMAN 3 Karawang and to identify the obstacles and challenges faced by BK teachers in carrying them out. The research employed a descriptive qualitative method, with data collected through direct observation and interviews with BK teachers and eleventh-grade students. The findings show that the implementation of BK services at SMAN 3 Karawang has been running quite well. BK teachers have provided various types of services, such as individual counseling, group counseling, and informational services, which have had a positive impact on students, particularly in overcoming learning difficulties and social problems. However, several challenges remain, including an imbalance between the number of BK teachers and students, limited time and facilities, and negative perceptions among some students regarding the role of BK services. Overall, the implementation of BK services at SMAN 3 Karawang aligns with educational objectives, namely supporting students’ holistic development across personal, social, academic, and career domains. To improve service effectiveness, it is recommended that the school enhance facilities, increase the number of BK teachers, and intensify socialization regarding the role and benefits of BK services among the school community. ABSTRAK Layanan Bimbingan dan Konseling (BK) merupakan bagian integral dari sistem pendidikan yang berfungsi membantu peserta didik dalam mengembangkan potensi diri, menyesuaikan diri dengan lingkungan, serta mengatasi berbagai permasalahan pribadi, sosial, akademik, maupun karier. Berdasarkan teori Prayitno (2004) dan Tohirin (2011), layanan BK mencakup fungsi pemahaman, pencegahan, pengentasan, dan pengembangan, yang secara keseluruhan bertujuan mendukung perkembangan peserta didik secara optimal. Penelitian ini bertujuan untuk mengetahui bagaimana implementasi layanan BK di SMAN 3 Karawang, serta mengidentifikasi kendala dan tantangan yang dihadapi guru BK dalam pelaksanaannya. Metode yang digunakan adalah metode kualitatif deskriptif, dengan teknik pengumpulan data berupa observasi langsung dan wawancara terhadap guru BK serta siswa kelas XI. Hasil observasi menunjukkan bahwa pelaksanaan layanan BK di SMAN 3 Karawang telah berjalan cukup baik. Guru BK telah melaksanakan berbagai bentuk layanan seperti konseling individu, konseling kelompok, dan layanan informasi yang memberikan dampak positif bagi siswa, terutama dalam mengatasi kesulitan belajar dan permasalahan sosial. Namun demikian, pelaksanaan layanan masih menghadapi sejumlah kendala, seperti keterbatasan jumlah guru BK dibandingkan jumlah siswa, keterbatasan waktu dan fasilitas, serta persepsi negatif sebagian siswa terhadap fungsi BK. Secara keseluruhan, implementasi layanan BK di SMAN 3 Karawang sudah berjalan sesuai dengan tujuan pendidikan, yaitu membantu siswa berkembang secara menyeluruh baik dari aspek pribadi, sosial, akademik, maupun karier. Untuk meningkatkan efektivitas layanan, disarankan agar sekolah memperkuat dukungan fasilitas, menambah tenaga BK, serta meningkatkan sosialisasi mengenai peran dan manfaat BK kepada seluruh warga sekolah.